In The Context of History-Literature Relations The Theme of History In New Turkish Literature (Poetry and Novel) - Mehmet Samsakçı (Tarih Dergisi)
History has always been one of the most productive and captivating subjects within the realm of art and literature. Art, as a means of comprehending, analyzing, and expressing the human experience, society, and the adventure of humanity throughout the ages, has examined and processed history as a rich source of ready-made materials. Despite the evolving conceptions of history in various eras, history has continued to remain the most soughtafter, favored, and abundant source of inspiration in literature to this day. This study offers a panoramic exploration of how history has been approached in Turkish poetry and novels from the Tanzimat to the present.